1973
DOI: 10.1128/jvi.11.3.372-377.1973
|View full text |Cite
|
Sign up to set email alerts
|

Prophage-Mediated Interference Affecting the Development of Bacillus subtilis Bacteriophage φe

Abstract: Bacteriophage 4e shows a reduced efficiency of plating on strains of Bacillus subtilis which are lysogenic for the temperate bacteriophage SP02. Although this phenomenon resembles prophage-mediated restriction observed in other bacteria, host-controlled modification of 4e was not observed. Mutants of 4e which plated with high efficiency on the lysogenic host were isolated. Although classical DNA restriction and modification systems have not been described in BaciUus *ubtilis, it has been observed that some str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

1974
1974
1986
1986

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…on September 4, 2020 by guest http://mmbr.asm.org/ Downloaded from ences, however. They integrate at different positions on the host genome (136,263), and have dissimilar immunities as evidenced by the fact that double lysogens are easily prepared (242). Moreover, mutants of SP02 and 4105 do not complement one another in appropriate mixed infections, and they do not undergo heterologous genetic recombination (267).…”
Section: Bacteriol Revmentioning
confidence: 99%
See 1 more Smart Citation
“…on September 4, 2020 by guest http://mmbr.asm.org/ Downloaded from ences, however. They integrate at different positions on the host genome (136,263), and have dissimilar immunities as evidenced by the fact that double lysogens are easily prepared (242). Moreover, mutants of SP02 and 4105 do not complement one another in appropriate mixed infections, and they do not undergo heterologous genetic recombination (267).…”
Section: Bacteriol Revmentioning
confidence: 99%
“…It has recently been found that two unrelated phages, 4e and 41, abortively infect a strain of B. subtilis which is lysogenic for the temperate phage SP02 (242,356). The plating efficiency of he on lawns of B. subtilis 168 (SP02) is a thousand times less than on strain 168.…”
Section: Tionmentioning
confidence: 99%
“…However, infection of the permissive host SC607 with phage sc607 in the presence of CM did not show any detectable difference in the plaque-forming ability as compared with the phage infection without CM. This type of interaction between phage sc607 and strain MLl-11 appears to resemble the bacteriophage interference in lysogenic cultures of B. subtilis (20,27) and prophage interference in Escherichia coli (2,3). Many factors cause abortive infection similar to the one seen in phage sc607-infected MLl-11; such as alteration of growth media, preinfection of bacteria with identical or different bacteriophages, lysogenic conversion, or prophage interference (1, 2, 15).…”
Section: Discussionmentioning
confidence: 99%
“…The DNA isolated from bacteria carrying N3 prophage was no more efficient in transforming the lysogenic strain than was DNA isolated from nonlysogenic bacteria. Restriction without modification has been reported in other systems (11,12,19). Watanabe et al (19) postulated that the restriction enzyme would have to be located away from the bacterial and plasmid DNA, possibly at a membrane site.…”
Section: Discussionmentioning
confidence: 99%